To simplify \((-\sqrt{-49} + 5i) + (8 - \sqrt{4})\), let's break it down step by step.
-
Simplify \(-\sqrt{-49}\): \[ -\sqrt{-49} = -\sqrt{49}i = -7i \]
-
Simplify \(-\sqrt{4}\): \[ -\sqrt{4} = -2 \]
-
Now substitute these back into the equation: \[ (-7i + 5i) + (8 - 2) \]
-
Combine like terms:
- For the imaginary parts: \[ -7i + 5i = -2i \]
- For the real parts: \[ 8 - 2 = 6 \]
-
Combine the results: \[ 6 - 2i \]
None of the provided responses match \(6 - 2i\). Please double-check the original expression and values to ensure correct classification and simplification.